The mainly South African genus Lanurgus revised (Coleoptera, Scolytinae) - Jordal, Bjarte H. (Zootaxa, 2021)
The Afrotropical and mainly southern African genus Lanurgus Eggers, 1920 is revised. Five new species are described from the Cape provinces in South Africa: Lanurgus beaveri, sp. nov., Lanurgus carinatus, sp. nov., Lanurgus jubatus, sp. nov., Lanurgus mattheei, sp. nov., and Lanurgus tsitsikammae, sp. nov. A molecular phylogenetic analysis of nine species revealed deep divergence between fairly morphologically similar species, with few clues on nested relationships within the genus. Photos and a key to all known species is presented.